Geoquímica de gnaisses do arco magmático de goiás na região sul do estado de goiás - Navarro, Guillermo Rafael Beltran [UNESP]; Zanardo, Antenor [UNESP] (My University, 2007)
Granitic to trondhjemitic gneisses from the Pontalina region in the southern part of Goiás State, Central Brazil, have calcic to calc-alkaline, metaluminous to peraluminous compositions. They have low concentrations of alkaline elements, and are enriched in Ba, Sr, K, Rb in relation to Nb, Y, Zr and REE, and have negative anomalies of Nb and Ti, features which are similar to those of magmas generated in magmatic arc environments. Those rocks were previously interpreted as part of the basement of the Brasília Belt, attributed to the Archean to Paleoproterozoic, but new Sm - Nd isotopic data indicate a neoproterozoic age (TDM = 0,9 a 1,2 Ga), and the preliminary geochemical data reveal compositions similar to the gneisses of the other regions belonging to the Goiás Magmatic Arc.
The geochemistry of the gneisses of the Goiás Magmatic Arc in the southern region of the Goiás State
Keywords: Brasilia belt; Geochemistry; Gneisses; Goiás magmatic arc; calc alkaline rock; geochemistry; gneiss; isotopic composition; magmatism; Brasilia Belt; Brazil; Goias; Pontalina; South America